Financial Distress pada Perusahaan Initial Public Offering (IPO) - Victoria Ari Palma Akadiati; Imelda Sinaga; Desiderius Novena Kosta (Universitas Batanghari Jambi, 2022)
Research on companies that conducted initial public offerings in 2018 was conducted with the aim of knowing the effect of cash flow, profit, total debt on financial distress. The sample selection was carried out by purposive sampling technique and is a qualitative research that uses multiple linear regression data analysis techniques using operating cash flow ratios, return on assets ratios, total debt using leverage and the Altman Z